Imaginário, memória e histórias de vida: narrativas biográficas de egressas do Asilo de Órfãs Felisbina Leivas - Aguiar, Priscila de Souza de (2014)
The present work has been developed within the group of studies and research about Imaginary, Education and Memory (GEPIEM). It is situated in the Research Line Written Culture, Languages and Learning of Post-Graduate Program of the Federal University of Pelotas, and approaches the issue of institutionalization of children in Brazil, under the perspective of women who were in “Felisbina Leivas’ Asylum”, located in Jaguarão/RS. The research discusses the life history of the children’s egresses of institution, based on studies by JOSSO and the ‘Imaginary’, from the perspective of MACHADO DA SILVA. The objective of this work is to reconstruct, by imagination, narratives of women that spend parts of their childhood or youth in that religion asylum institution. The research seeks analyze and understand linked marks from the time that they have been stayed in the Home, taking as corpus analysis of their life histories. The biographical narratives were used as the main methodological tool to understand how the founding images, from the imagination, drive/influence living thing (a person who lives at the present time) of these women, besides to show the educational processes. The route methodological occurred in three instances: the first was operationalized by visits in the orphanage, with egresses, where have been recorded, photographic or not, images from a trigger question: 'Register images that marked you positively or negatively'. In the second, I change their biographical narratives in stories, what I call 'make history' (textualization). After transcription and textualization of narratives, I began a process of transcreation, with which I tried to bring the reader to the world of sensations caused by contact with the protagonists of the research. The third, and last, occurred so that verifies and checks two focuses: foundational images and educational practices. The empirical study showed that learning and incorporation of the rules was done by the interaction; work for maintenance and cleaning of the Home was part of the routine of girls; the school was present in their daily lives and is strongly valued; cope deal with the family’s absence is also need. The founding pictures identified in the three narratives are strongly associated with the role and image of mother, and the overvaluation of the presence of this figure, the perception of abandonment or the recognition of the importance to devote love to their sons and daughters. The fundamental appointed the empirical research, was that even with all the reverses of negative experiences at Home, this was established as a place of protection, which provided security for whom there had guarded his life.